Synthesis and Characterization of Novel Methyl 2-(1,7,7-Tri methylbicyclo[2.2.1]hept-2-yieldene)hydrazinecarbodithioate Schiff Bases Derived From Methylhydrazine carbodithioate And Their Bi(III) And Ag(II) Complexes (Baghdad Science Journal, 2025)
Novel bidentate Schiff bases having nitrogen-sulphur donor sequence was synthesized from condensation of racemate camphor, (R)-camphor and (S)-camphor with Methyl hydrazinecarbodithioate (SMDTC). Its metal complexes were also prepared through the reaction of these ligands with silver and bismuth salts. All complexes were characterized by elemental analyses and various physico-chemical techniques. These Schiff bases behaved as uninegatively charged bidentate ligands and coordinated to the metal ions via ?-nitrogen and thiolate sulphur atoms. The NS Schiff bases formed complexes of general formula, [M(NS)2] or [M(NS)2.H2O] where M is BiIII or AgI, the expected geometry is octahedral for Bi(III) complexes while Ag(I) is expected to oxidized to Ag(II) forming square planner complexes.